(untitled) (Canadian Allergy & Immunology Today, 2025)
Hereditary angioedema (HAE) is a rare genetic disorder caused by a deficiency or dysfunction in the serine protease inhibitor of C1, which results in an accumulation of the vasodilator bradykinin. Angioedema is a type of temporary swelling that can be histaminergic (mast cell-mediated) or non-histaminergic (bradykinin-mediated), of which HAE is an example. The prevalence of HAE is approximately 1:50,000 individuals, and no major differences in prevalence between ethnicities or sex have been reported for the most common subtypes I and II. There are three categories of HAE; type I is the most prevalent and is characterized by low C1-inhibitor (C1-INH) levels, type II ischaracterized by normal levels but low activity of C1-INH (dysfunctional C1-INH), and patients with the nC1-INH subtype have normal C1-inhibitor levels and function. This last subtype has an unknown prevalence, but is less commonly observed than type I and II. The dysfunction or deficit in C1-INH results in accumulation of the vasodilator bradykinin. C1-INH is involved in inhibiting proteins in the bradykinin pathway, such as factor XIIa and kallikrein. Due to the overproduction of bradykinin, vascular permeability increases, resulting in recurrent episodes of potentially severe angioedema in various body parts (HAE attacks). HAE management includes acute attack management, and potentially short-term and/or long-term prophylaxis (LTP). This article will discuss disease burden, patient unmet needs, challenges with conventional treatments, and clinical trial and real-world experience with the newer LTP agents lanadelumab, berotralstat, and garadacimab, with a particular emphasis on Canadian experience with these newer drugs.